Pengukuran keanekaragaman makrozoobenthos di perairan dataran banjir sungai Rungan Kalimantan Tengah menggunakan substrat buatan dari ijuk. - Bambang Sulistiyarto (Fakultas Peternakan Universitas Kristen Palangka Raya, 2015)
This study aims to measure the diversity of benthic macroinvertebrate in Rungan river floodplains using artificial substrates from palm sugar fibres. Sampling of benthic macroinvertebrate using artificial substrates made from palm sugar fibres which were incubated in waters for 14 days. Benthic macroinvertebrate which colonize in artificial substrate includes 21 species were consist of 19 species of insects class, 1 species of class Oligochaeta, and 1 species was not identified. The diversity of benthic macroinvertebrate in Rungan river floodplains was high with Shannon index (H ') = 3.1482. Evenness index (E) = 0.7243 indicates that benthic macroinvertebrate communities are not dominated by a certain species. Benthic macroinvertebrate communities in Rungan river floodplains were in a healthy condition, so it can support ecological systems in these waters. Key words : Benthic macroinvertebrate, diversity, floodplain, artificial substrat. floodplain.